Evidence from Risk Management in Software Product Lines development: A Cross-Case Analysis - Lobato, Luanna Lopes; Silveira Neto, Paulo Anselmo da Mota; Machado, Ivan do Carmo; Almeida, Eduardo Santana de; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
Software Product Line Engineering (SPLE) is a paradigm in software development that enables rapid development of new applications, by means of systematically reusing assets. To take effect and deliver the promised benefits, SPLE demands for substantial upfront investments, and manageable processes. Such a scenario leads to the need of a rigorous risk management, to be employed with the aim of decreasing the impact of problems that may occur during the projects' development, thus improving the use of resources. This work presents an analysis of two case studies of Risk Management practices in software product line projects, carried out in academic and industry settings. In order to synthesize evidence and increase validity of the results, the outcomes were compared by means of a cross-case analysis, in which we analyzed the identified risks, their assessment and the activities used to mitigate them. The results were mapped to highlight the insights in both studies.